2019
DOI: 10.1016/j.anr.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation in Patient Safety and Its Relationships with Nurses' Patient-Centered Care Competency, Teamwork, and Safety Climate

Abstract: This study's aim was to examine degrees of patient participation in patient safety activities in hospitals and to investigate their relationships with nurses' patient-centered care competency (PCC), teamwork, and safety climate. Methods: A cross-sectional study design was used. Data were collected with 479 nurses from two general hospitals in Seoul, Korea, using a questionnaire designed to collect data on patient participation in patient safety activities, PCC, teamwork perceptions, and safety climate. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 27 publications
(71 reference statements)
3
44
0
20
Order By: Relevance
“…This paper further highlights the importance of promoting nurses’ perusal of continuing competencies, as well as initiating nursing leadership in the health policy domain [ 75 ]. Future directions for healthcare reform should place emphasis on building nurses’ competency and expertise for patient-centered care, rather than disrupting the nurses’ specialty constructs [ 76 ]. Implementation of expansion and enhancement of the nurses’ specialty constructs through mandatory education, competencies and skill demonstrations are recommended to minimize the effects of work environment on patient and nurse outcomes [ 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…This paper further highlights the importance of promoting nurses’ perusal of continuing competencies, as well as initiating nursing leadership in the health policy domain [ 75 ]. Future directions for healthcare reform should place emphasis on building nurses’ competency and expertise for patient-centered care, rather than disrupting the nurses’ specialty constructs [ 76 ]. Implementation of expansion and enhancement of the nurses’ specialty constructs through mandatory education, competencies and skill demonstrations are recommended to minimize the effects of work environment on patient and nurse outcomes [ 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective teamwork in healthcare not only augments patient's satisfaction but also decreases burnout among the health professionals. [1][2][3][4] The Agency for Healthcare Research and Quality (AHRQ), the Joint Commission and other institutions ranked teamwork as a dominant factor for enhancing the healthcare quality. 5 6 Furthermore, teamwork has been classified as an important competency to help optimise the healthcare services and poor teamwork could increase the medical errors and reduce patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Smith & Liles, 2007). Many reports have shown that patient participation, patient safety, patients’ rights, patient-centeredness, and patient empowerment are intricately linked (Castro, Van Regenmortel, Vanhaecht, Sermeus, & Van Hecke, 2016; Hwang, Kim, & Chin, 2019; WHO, 2013). It is therefore essential to encourage patient everywhere to be knowledgeable and vigilant during treatment and care (WHO, 2013).…”
Section: Discussionmentioning
confidence: 99%